Penerapan Data Mining Dalam Pengelompokan Data Nilai Siswa SMA Negeri 7 Kota Bengkulu Menggunakan Metode K-Means Clustering - Achmad Rudi Antoni; Devi Sartika; Dimas Aulia Trianggana (Jurnal Media Infotama, 2025)
SMA Negeri 7 Kota Bengkulu is one of the State Senior High SchoolsState Senior High School located in Bengkulu City which has a commitment to in developing student potential. So far, data processing of student grades for each subjects have used e-report cards and the report card data can be exported to a Microsoft Excel file. exported into a Microsoft Excel file. However, the student grade data is data is often only stored as an archive without any further analysis to find out to find out information about patterns or trends in student achievement. At where this can help the school in providing guidance and optimizing the academic potential of each student at SMA Negeri 7. optimize the academic potential of each student at SMA Negeri 7 Bengkulu City based on the level of student achievement. Bengkulu City based on student achievement levels. Application of data mining in grouping data grades of SMA Negeri 7 Bengkulu City students using the K-Means Clustering Method is built desktop-based with the Visual Basic .Net programming language. Visual Basic .Net programming language, The application of data mining in grouping data in clustering student grades of SMA Negeri 7 Bengkulu City is carried out per student subject with subject value attributes and attendance percentage. The application of data mining in clustering student grade data of SMA Negeri 7 Bengkulu City can help in knowing the level of achievement of students of SMA Negeri 7 Bengkulu City. Bengkulu City can help in knowing the level of student achievement in each subject and can be used as an evaluation material to improve the level of student achievement in each subject. subjects and can be used as evaluation material to improve the achievement of students who are at low achievement levels. who are at a low level of achievement.